2012
DOI: 10.1038/ismej.2012.79
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic stratigraphy in the Guerrero Negro hypersaline microbial mat

Abstract: The microbial mats of Guerrero Negro (GN), Baja California Sur, Mexico historically were considered a simple environment, dominated by cyanobacteria and sulfate-reducing bacteria. Culture-independent rRNA community profiling instead revealed these microbial mats as among the most phylogenetically diverse environments known. A preliminary molecular survey of the GN mat based on only ∼1500 small subunit rRNA gene sequences discovered several new phylum-level groups in the bacterial phylogenetic domain and many p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
211
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(223 citation statements)
references
References 39 publications
11
211
0
1
Order By: Relevance
“…Of these include the comparable microbial mats of Guerrero Negro (Baja California Sur, Mexico), which have historically been of keen interest as spatially stratified, highly diverse model microbial ecosystems (Canfield and Des Marais, 1993;Risatti et al, 1994;Ley et al, 2006). A previous study reported increasing OTU counts with depth over the first 3 mm of the Guerrero Negro mat (Harris et al, 2013). Although depth profiles of productivity were not explicitly measured, higher-species richness presumably corresponded with lower rates of photosynthesis than would be observed at the mat's surface.…”
Section: Diversity-productivity Relationshipsmentioning
confidence: 99%
“…Of these include the comparable microbial mats of Guerrero Negro (Baja California Sur, Mexico), which have historically been of keen interest as spatially stratified, highly diverse model microbial ecosystems (Canfield and Des Marais, 1993;Risatti et al, 1994;Ley et al, 2006). A previous study reported increasing OTU counts with depth over the first 3 mm of the Guerrero Negro mat (Harris et al, 2013). Although depth profiles of productivity were not explicitly measured, higher-species richness presumably corresponded with lower rates of photosynthesis than would be observed at the mat's surface.…”
Section: Diversity-productivity Relationshipsmentioning
confidence: 99%
“…Strain SCBM T shared only 91.7 % pairwise 16S rRNA gene sequence identity with its closest cultured phylogenetic relative, Desulfarculus baarsii DSM 2075 T , while similarities to other recognized species in the class Deltaproteobacteria were ¡87 %. The next most closely related, described relatives of strain SCBM T were Desulfatibacillum alkenivorans AK-01 (87 % similarity), Desulfomonile tiedjei DSM 6799 T (87 %), Desulfatibacillum aliphaticivorans CV2803 T (87 %), Desulfovibrio cavernae H1M (87 %), Desulfobacterium anilini Ani1 T (86 %), Desulfococcus oleovorans Hxd3 (86 %), Desulfosalsimonas propionicica PropA T (86 %) and Desulfatitalea tepidiphila (Harris et al, 2013); 65-OC-8 (93 %; HE797781), retrieved from an anoxic brackish photosynthetic biofilm at Berre Pond, France; UASB-TL19 (93 %; AF254400), recovered from a 4-methylbenzoatedegrading methanogenic consortium (Wu et al, 2001);and 624H2B-13, 624H2B-24 and 624H2B-36 (93 %;KC408551, KC408562 and KC408572, respectively), retrieved from coalbed water from Qinshui Basin, China. We suggest that the unique coal environment from which our isolate was retrieved may have enriched microorganisms such as strain SCBM T and that such bacteria may be important members of the microbial community involved in anaerobic carbon metabolism in coal beds.…”
Section: Genotypic Characterizationmentioning
confidence: 99%
“…A current synthesis of the available data suggests that JS1 is a characteristic denizen of subseafloor environments, and is particularly abundant in sediments associated with methane hydrates and hydrocarbon seeps, and on continental margins and shelves (Inagaki et al, 2006;Orcutt et al, 2011;Parkes et al, 2014). Sequences related to JS1 have also been detected in environments such as petroleum reservoirs (Pham et al, 2009;Kobayashi et al, 2012), hypersaline microbial mats (Harris et al, 2013), and landfill leachates (Liu et al, 2011). The phylogenetic relationships between OP9, JS1 and other bacterial phyla have not been fully resolved (McDonald et al, 2012), and to date, no axenic cultures have been reported for either of these lineages, although enrichment cultures containing JS1 have been successfully obtained (Webster et al, 2011).…”
Section: Introductionmentioning
confidence: 99%